Universidade Federal do Espírito Santo na ditadura civil-militar (1964-1985): um olhar sobre as histórias de repressões e lutas - Viana, Vivian Jaciara (2023)
From 1964 onwards, Brazil experienced an exceptional regime marked by authoritarianism, when the State implemented anti-democratic reforms aimed at legitimizing the political, economic and ideological interests of the groups that supported the coup. The present work investigates the actions of repression and censorship that took place within the Federal University of Espírito Santo (UFES) during the civil-military dictatorship (1964-1985), based on a bibliographical and documental analysis. This includes an observation of actions taken by the University administration and the impact of the dictatorship on academic freedom and student activism. During this period, the government sought to exert control over universities and other institutions of higher learning, in part to stifle dissent and criticism of the regime. The adopted methodology is based on bibliographical and documentary research, which help us to understand how the political repression of the Civil-Military Dictatorship period affected the education of the subjects and their formation at UFES. As for the theoretical framework, we will work with historical-dialectical materialism, which helped us to understand our object of study, relating the particular (UFES) with the totality (Brazil), providing a critical analysis of the circumstances. We were able to conclude that the student movement played a prominent role throughout the dictatorial period, with several student demonstrations repressed with violence. Repression during the period of the Civil-Military Dictatorship influenced student activism, causing an inhibiting effect on student participation in social and political movements, leading to a decline in student mobilization and organization around issues of social justice and democracy.